Histone lysine trimethylation or acetylation can be modulated by phytoestrogen, estrogen or anti-HDAC in breast cancer cell lines. (February 2013) - Dagdemir, Aslihan; Durif, Julie; Ngollo, Marjolaine; Bignon, Yves-Jean; Bernard-Gallon, Dominique
Aim: The isoflavones genistein, daidzein and equol (daidzein metabolite) have been reported to interact with epigenetic modifications, specifically hypermethylation of tumor suppressor genes. The objective of this study was to analyze and understand the mechanisms by which phytoestrogens act on chromatin in breast cancer cell lines.Materials & methods: Two breast cancer cell lines, MCF-7 and MDA-MB 231, were treated with genistein (18.5 µM), daidzein (78.5 µM), equol (12.8 µM), 17β-estradiol (10 nM) and suberoylanilide hydroxamic acid (1 µM) for 48 h. A control with untreated cells was performed. 17β-estradiol and an anti-HDAC were used to compare their actions with phytoestrogens. The chromatin immunoprecipitation coupled with quantitative PCR was used to follow soy phytoestrogen effects on H3 and H4 histones on H3K27me3, H3K9me3, H3K4me3, H4K8ac and H3K4ac marks, and we selected six genes ( EZH2, BRCA1, ER α, ER β, SRC3 and P300 ) for analysis.Results: Soy phytoestrogens induced a decrease in trimethylated marks and an increase in acetylating marks studied at six selected genes.Conclusion: We demonstrated that soy phytoestrogens tend to modify transcription through the demethylation and acetylation of histones in breast cancer cell lines.